Targeting APE1/Ref-1 to alleviate formalin-induced pain and spinal neuro-inflammation in rats: a promising therapeutic approach - Elgendy, Eman; Zaky, Amira; Wahby, Mayssaa; Landry, Marc; Bassiouny, Ahmad (Frontiers in Neuroscience, 2025)
BackgroundPain is a multifaceted condition intricately linked to inflammation, which plays a critical role in its onset and progression.MethodsTo investigate the influence of APE1/Ref-1 on oxidative stress and inflammatory marker expression, we employed a hind paw sensitization model induced by formalin. We inhibited the redox function of APE1 using E3330 and assessed its effects on pain behavior. Mitochondrial morphology was examined via electron microscopy, and the impact on dopaminergic signaling alongside bioinformatics analyses to explore potential E3330 binding to dopamine receptors.ResultsAdministration of E3330 in formalin-induced rats resulted in improved pain thresholds, as evidenced by behavioral assessments. Notably, E3330 treatment maintained normal APE1/Ref-1 levels and promoted a more organized mitochondrial structure. Administration of E3330 correlated with increased dopamine levels, a decrease in the mRNA expression of dopamine receptors DRD1 and DRD5, and a restoration of DRD2 expression in the ipsilateral spinal cords. Moreover, E3330 administration significantly reduced the expression of key inflammatory mediators including inflammasome markers. Our bioinformatics analysis using Molecular Operating Environment software indicated that E3330 possibly interacts with critical active sites within specific dopamine receptor pocket as preliminary results.ConclusionThese findings suggest that E3330 may modulate pain signaling pathways from the periphery to the spinal cord, offering a novel approach for the management of inflammatory pain conditions, potentially through the modulation of the dopaminergic signaling pathway. Further research is warranted to elucidate E3330’s role in regulating central nervous system pain signal transmission, as it emerges as a promising therapeutic candidate in clinical contexts.